Hyperglycemia and Cholesterol Surge in Iraqi Diabetic Patients: Hiperglikemia dan Lonjakan Kolesterol pada Pasien Diabetes di Irak - Afak Rasheed Salman Zaidi; Ali abbas Ali (Academia Open, 2024)
Diabetes mellitus, a metabolic disorder characterized by abnormal hyperglycemia, often correlates with dyslipidemia. This study examined the relationship between random blood sugar (RBS) levels and cholesterol types (HDL, LDL, and total cholesterol) in 350 patients from Diyala, collected between February and April 2023. Results showed higher blood sugar levels in females (22.3%) than males (19.7%) among the elderly (≥60 years). Type 2 diabetes was more prevalent than type 1 (77% vs. 5.4%). Cholesterol levels were elevated in 26% of patients. RBS was high in 82% of patients, and 49% had elevated total cholesterol. Both age groups 41-60 and ≥60 had high hyperglycemia incidence (32%), with higher prevalence in females (40.6%) compared to males (35.7%). These findings underscore the need for targeted interventions to manage blood sugar and cholesterol levels. Highlights: Prevalence: Type 2 diabetes is significantly more common than type 1 among patients in Diyala. Gender Disparity: Females exhibit higher blood sugar and cholesterol levels compared to males. Age Impact: Elevated blood sugar is prevalent in both middle-aged and elderly populations, necessitating targeted interventions. Keywords: Diabetes Mellitus, Hyperglycemia, Cholesterol, Insulin Resistance, Dyslipidemia